2007
DOI: 10.1007/s10152-007-0092-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term variability of winter nitrate concentrations in the Northern Wadden Sea driven by freshwater discharge, decreasing riverine loads and denitrification

Abstract: The hypothesis of a recent reversal in the eutrophication of the Wadden Sea and the potential of inshore waters in denitrification is explored. Salinity, temperature and nitrate concentrations in the List Tidal Basin (Northern Wadden Sea) have been measured about twice weekly since 1984. Salinity has a clear seasonal cycle with lowest salinities of about 27 in late winter and highest salinities of about 31 in summer. Mean annual deviations from the long-term mean salinity correlate significantly with riverine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 38 publications
3
19
1
Order By: Relevance
“…Moreover, weather-dependent fluctuations in the residence time of Wadden Sea tidal water masses have recently been hypothesised as pivotal in controlling regional eutrophication (van Beusekom et al 2008), and is has been shown that pore waters from tidal flats represent an important part of the nutrient and carbon cycle in the North Sea (Billerbeck et al 2006a, b). Therefore, additional tracers that could improve evaluations of groundwater and pore water discharge, water mass residence times or exchange rates would be a useful tool in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, weather-dependent fluctuations in the residence time of Wadden Sea tidal water masses have recently been hypothesised as pivotal in controlling regional eutrophication (van Beusekom et al 2008), and is has been shown that pore waters from tidal flats represent an important part of the nutrient and carbon cycle in the North Sea (Billerbeck et al 2006a, b). Therefore, additional tracers that could improve evaluations of groundwater and pore water discharge, water mass residence times or exchange rates would be a useful tool in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…The N 2 O emission potential of marine invertebrates has so far been neglected, although coastal marine sediments are presumably hot spots of N 2 O emission, since they are densely inhabited by filter-and depositfeeding invertebrates (Williams et al 2004, Philippart et al 2007) and exposed to high nitrate concentrations (Kieskamp et al 1991, Van Beusekom et al 2008. High N 2 O emission can also be expected from aquaculture facilities in which animals are typically reared at high densities and high nitrate concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to a reduction in nutrient input (Hickel et al 1993;van Beusekom 2004;van Beusekom et al 2008) and also due to the fact that the current direction is less influenced by coastal waters, and more open North Sea water reaches the site than 45 years ago (Fig. 6).…”
Section: Nutrientsmentioning
confidence: 99%